A cobalt Schiff base complex on TiO2 nanoparticles as an effective synergistic nanocatalyst for aerobic C–H oxidation. Issue 30 (7th March 2016) - Jafarpour, Maasoumeh; Kargar, Hossein; Rezaeifard, Abdolreza
Abstract : A cobalt Schiff base complex on TiO2 nanoparticles possess excellent photocatalytic properties under visible light for the aerobic benzylic C–H oxidation. Abstract : A novel visible light active TiO2 nanoparticle was produced by functionalization with a cobalt Schiff base complex under ultrasonic agitation. It was characterized by different techniques such as FT-IR, EDX, XPS, ICP-AES and TGA. The particle size of the synthesized nanocomposite was found to be in the range of 22–32 nm according to TEM images. A red-shift of the band-edge and a significant reduction of the band-gap (2.9 eV) were revealed by UV-DRS. The as-prepared nanocomposite demonstrated high oxidation activity and desired selectivity in the aerobic benzylic C–H oxidation of a structurally diverse set of alcohols and benzylic hydrocarbons. A synergistic effect of the cobalt Schiff base complex and TiO2 nanoparticles on the visible-light photocatalytic activity was explored. Spectral results and leaching experiments revealed that the heterogeneous catalyst preserved its structure after many reuses.